2021
DOI: 10.1080/21678421.2021.1879866
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for Multi-National Investigator-Initiated clinical trials for ALS: European and United States collaborations

Abstract: An inherent challenge to clinical trials that aim to test the efficacy of experimental therapeutics for patients with amyotrophic lateral sclerosis (ALS) is the relative rarity of the disease. A promising solution to this problem is a multi-center approach that ideally includes sites distributed across a broad geographic area. In support of such an approach, the European E-RARE program and the United States National Institutes of Health (NIH) partnered to support the investigator-initiated ROCK-ALS trial (Eudr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Because authorship has grown exponentially but the number of joint publications has only climbed linearly, it is suggested that connection is deepening. Changing cooperation patterns in Europe are believed to be a result of the European Commission's Framework Programmes' cohesion elements, which promote multi-national collaborations regardless of scientific quality [ 43 ]. VOSviewer was used in this study to visualize the co-authorship between authors.…”
Section: Resultsmentioning
confidence: 99%
“…Because authorship has grown exponentially but the number of joint publications has only climbed linearly, it is suggested that connection is deepening. Changing cooperation patterns in Europe are believed to be a result of the European Commission's Framework Programmes' cohesion elements, which promote multi-national collaborations regardless of scientific quality [ 43 ]. VOSviewer was used in this study to visualize the co-authorship between authors.…”
Section: Resultsmentioning
confidence: 99%
“…In extension to UK–EU database recognition, there is also a need for regulatory acceptance of equivalent international databases, facilitated through the World Health Organization International Clinical Trials Registry Platform, 61 to include guaranteed and accepted standards for anonymity protection for the personal data of patients and trial participants between the UK and the US. 62 , 63 …”
Section: Discussionmentioning
confidence: 99%
“…21 24 This required additional administrative steps. 24 To overcome these challenges, INSIGHT (International Network for Strategic Initiatives in Global HIV Trials) established coordinating centres in several countries that were geographically closer to sites, familiar with local regulatory requirements and fluent in local languages which improved the contract negotiation process. 23…”
Section: Open Accessmentioning
confidence: 99%